Predicting rates of manganese oxide reduction from thermodynamic driving forces and structural properties - Xinru Liu; Vineeth Pothanamkandathil; Lorenz Schwab; Shun Mao; Meret Aeppli (Proceedings of the National Academy of Sciences, 2026)
Manganese (oxyhydr)oxides are abundant redox-active minerals that influence diverse biogeochemical processes, yet their redox reactivity remains poorly understood due to variations in mineral structure and manganese oxidation state. We quantified the reduction kinetics of three geochemically relevant manganese oxides—birnessite, manganite, and hausmannite—using extracellular electron shuttles with varying redox potentials to systematically modulate the driving force for electron transfer. While the Gibbs free energy ( Δ r G ) described the kinetics of individual oxides well, the Pourbaix free-energy difference ( Δ Ψ ) offered a distinct advantage by predicting reactivity without requiring detailed knowledge on reaction pathways, making it especially valuable for systems where exact redox reactions are undefined. We further developed a coupled kinetic-mass transport model, which showed that electron-transfer rate constants varied among oxides, whereas mass-transfer coefficients were similar. Classical nucleation theory was applied to contextualize these differences, indicating that the balance between surface and bulk energies controls the dissolution barrier. Our findings not only demonstrate how reaction thermodynamics and phase differences jointly control manganese oxide reduction kinetics but also support a generalizable predictive framework for the reactivity of redox-active minerals across diverse environmental conditions.